Mortality Clustering in the Family. Fast Life History Trajectories and the Intergenerational Transfer of Infant Death in Late 19th- and Early 20th-Century Antwerp, Belgium - Robyn Donrovich; Paul Puschmann; Koen Matthijs (Historical Life Course Studies)
In this article, we investigate to what degree infant mortality risk was transferred from grandmothers to mothers in the Antwerp district, Belgium, during the late nineteenth and early twentieth century. We also investigate some of the determinants of infant mortality and explore the role of the family - paternal factors (presence, age, and social class), mother’s childcare experience, and infant household location - in the survival of infants. The data for this research were retrieved from the Antwerp COR*-database and were transferred into the Intermediate Data Structure (IDS). The results of the survival models show that women whose mother experienced three or more infant deaths had a 77% higher risk of experiencing the loss of an infant themselves, compared to women whose mother experienced zero infant deaths in the past. These results remained robust after controlling for potential mediating and moderating factors. The results on the age of the mother at birth, her marital status, as well as the living environment suggest that at least part of the intergenerational transfer in infant mortality can be explained on the basis of life history theory: women who grew up in a high-risk family tended to reproduce earlier and faster, and often raised their children without a partner. In this way they unconsciously created riskier conditions for the raising of their own infants: the mothers had little life experience, limited resources, and often no assistance from a partner. As a result, their own children were also at an increased risk of dying in infancy.